Salisbury Cathedral
After removing from Old Sarum the new cathedral, building on the banks of the Avon at Salisbury proceeded at a great pace. Construction began at the east end with what at other establishments would be the Lady Chapel. Black Purbeck marble shafts, 30 feet in height, support a simple quadripartite vaulted roof, and the space is lit by triple lancet windows very different from the later geometric lancet of the Lincoln choir. The glass in these windows, as with so much of England's medieval stained glass, is replaced with modern work: this is by Christopher Webb.